Edukasi Peningkatan Kinerja Dengan Pelatihan Pencatatan Laporan Keuangan Pada Wirausahawan - Widiastuti Widiastuti; Zulfa Zakiatul Hidayah; Indra Permana; Army Cahya Putra Rustamaji; Dian Rachmawati Afandi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Financial management is very crucial in practice, both personal and business financial management. This is very important, especially for MSMEs, because poor financial management will have an impact on bookkeeping and make income and expenses confusing, especially if the business being run has started to increase in sales. Financial recording is an important thing but is often underestimated even though there are many benefits that entrepreneurs get by recording financial reports. There are many reasons why a business has not recorded financial reports properly, such as a lack of insight into what it is like to make or record its own financial reports and there are no resources that can handle it, as is also felt by the entrepreneur who owns the Tunas Sari semprong located in Rengasdengklok-Karawang. Starting from this, in this community service, we aim to provide basic training in simple financial recording to improve the performance of entrepreneurs' businesses. Apart from the manual, we also provide understanding in operating financial records using a digital application in the form of BukuKas which can be installed on business people's smartphones. This makes it easier for entrepreneurs to operate financial reports. With knowledge of financial reports, we can easily find out our income and expenses and can be used as evaluation material in improving business performance and developing the business we own. From the results of this training, it is hoped that entrepreneurs will be able to record simple financial reports and be able to operate the BukuKas application to make recording easier.